CONTENT OF NUTRIENTS AND SILICON IN LEAF OF RICE PLANTS INFECTED BY Bipolaris oryzae - ZANÃO JÚNIOR, Luiz Antônio; FONTES, Renildes Lúcio Ferreira; ÁVILA, Vinícius Tavares de (Scientia Agraria, 2010)
Changes in the levels of macro and micronutrients in diseased plants are reported in several crops. The occurrence of changes in nitrogen, phosphorus, potassium, calcium, magnesium, copper, iron, manganese, zinc and silicon contents were evaluated in leaves of rice plants infected with the Bipolaris oryzae fungus, which causes the brown spot disease, important rice disease in Brazil and worldwide. The treatments were the inoculation or not of the plants with the Bipolaris oryzae fungus.The design adopted was completely randomized, with ten repetitions. The Bipolaris oryzae fungus causes decrease in the nitrogen foliar content and increase in the managnese foliar content in the rice plants.